Beyond The Plate: Exploring The Impact Of The National School Nutrition Programme On Educational Access For Grade 3 Learners In King Sabata Dalindyebo Municipality - Ndamase, Zona; Mofolo, Malefetsane (Journal of Ecohumanism, 2025)
School feeding programmes are globally recognised as critical interventions for addressing childhood hunger and supporting learning outcomes; however, their impact often extends beyond providing meals. This qualitative study examines how the National School Nutrition Programme (NSNP) influences educational access for Grade 3 learners in King Sabata Dalindyebo Municipality, Eastern Cape. The study uses semi-structured interviews with teachers, parents, and school cooks to analyse the social, educational, and institutional dimensions that shape the programme’s effectiveness. Guided by Bronfenbrenner’s Ecological Systems Theory, the findings demonstrate that at the classroom level, daily meals improve concentration, attentiveness, and participation, while reducing absenteeism. Collaboration between schools, families, and communities further enhances programme delivery, though challenges such as delayed food supply, inadequate infrastructure, and insufficient funding undermine consistency. Despite these barriers, the NSNP is vital in alleviating food insecurity, promoting learner wellbeing, and advancing equitable education in rural communities. By going “beyond the plate,” the study underscores the need for stronger policy support and community engagement to sustain the transformative impact of school feeding initiatives.